2012
DOI: 10.1371/journal.pone.0037218
|View full text |Cite|
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Enhances Satellite Cell Activation in Dystrophic Muscles through a S1PR2/STAT3 Signaling Pathway

Abstract: Sphingosine-1-phosphate (S1P) activates a widely expressed family of G protein-coupled receptors, serves as a muscle trophic factor and activates muscle stem cells called satellite cells (SCs) through unknown mechanisms. Here we show that muscle injury induces dynamic changes in S1P signaling and metabolism in vivo. These changes include early and profound induction of the gene encoding the S1P biosynthetic enzyme SphK1, followed by induction of the catabolic enzyme sphingosine phosphate lyase (SPL) 3 days lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 79 publications
8
104
1
1
Order By: Relevance
“…Alternatively, and most likely, high SPL expression is required in tissues subjected to high S1P biosynthesis or uptake. Mice with reduced global SPL activity exhibit high levels of S1P in most tissues in comparison to control mice, as shown by others and ourselves ( 31,40,42,44,46 ). Even in tissues such as heart and skeletal muscle, wherein baseline SPL levels are very low to undetectable, SPL inhibition has signifi cant effects on S1P levels.…”
Section: Expression Of Spl During Murine Developmentmentioning
confidence: 71%
See 2 more Smart Citations
“…Alternatively, and most likely, high SPL expression is required in tissues subjected to high S1P biosynthesis or uptake. Mice with reduced global SPL activity exhibit high levels of S1P in most tissues in comparison to control mice, as shown by others and ourselves ( 31,40,42,44,46 ). Even in tissues such as heart and skeletal muscle, wherein baseline SPL levels are very low to undetectable, SPL inhibition has signifi cant effects on S1P levels.…”
Section: Expression Of Spl During Murine Developmentmentioning
confidence: 71%
“…However, we have shown that SPL is induced in the murine heart and skeletal striated muscle in response to ischemia and chemical injury, respectively ( 44,46 ). SPL expression is regulated by transcriptional and post-transcriptional mechanisms during development and in response to radiation, ischemia and other insults.…”
Section: Expression Of Spl During Murine Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…1d, middle panel). After these results, we hypothesized that neuronal S1PR1 could be involved in the control of the energy homeostasis through the positive cross-talk mechanism, involving Jak/STAT3 cascade in neurons, as observed in other cell types [11][12][13][14]17 .…”
Section: Resultsmentioning
confidence: 88%
“…16). S1P/S1PRs axis plays a important role in the control of cardioprotection 11 , intestinal inflammation 12 , satellite cell activation 17 and tumour cells progression 13 through the persistent STAT3 activation. However, the role of hypothalamic S1P/S1PR1/STAT3 axis in the control of the energy homeostasis was not reported.…”
mentioning
confidence: 99%